2008
DOI: 10.3121/cmr.2008.788
|View full text |Cite
|
Sign up to set email alerts
|

Applying Case Definition Criteria to Irritable Bowel Syndrome

Abstract: Irr itable bowel syndrome (IBS) is a functional disorder of the gastrointestinal tract characterized by recurrent episodes of abdominal pain or discomfort along with changes in frequency or consistency of the stool in the absence of an organic etiology. The condition is heterogeneous, exhibiting variability in the frequency of symptoms reported within and between males and females. 1 The pathophysiological mechanisms of IBS are not completely understood. Alterations in gut motility, visceral perception, and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
0
15
0
1
Order By: Relevance
“…This condition, estimated to have 5–25% prevalence in the world population, again more frequently reported for the female gender, is not presently clarified in terms of patho-physiological mechanism, and is diagnosed exclusively according to symptom classification-based guidelines and exclusion of other known causes of organic pathologies, such as celiac or colon cancer diseases [82]. IBS is a heterogeneous condition presenting very frequent co-morbidity with other disturbances, mainly migraine headache, fibromyalgia and chronic pelvic pain, anxiety and depression, somatization, stress sensitivity, with consequent low quality-of-life scores bearing relevant socioeconomic impact [83].…”
Section: Controversial Case Definitionsmentioning
confidence: 99%
“…This condition, estimated to have 5–25% prevalence in the world population, again more frequently reported for the female gender, is not presently clarified in terms of patho-physiological mechanism, and is diagnosed exclusively according to symptom classification-based guidelines and exclusion of other known causes of organic pathologies, such as celiac or colon cancer diseases [82]. IBS is a heterogeneous condition presenting very frequent co-morbidity with other disturbances, mainly migraine headache, fibromyalgia and chronic pelvic pain, anxiety and depression, somatization, stress sensitivity, with consequent low quality-of-life scores bearing relevant socioeconomic impact [83].…”
Section: Controversial Case Definitionsmentioning
confidence: 99%
“…Rectal examination is useful in detecting retrorectal masses 4. Misinterpretation of symptoms and diagnosis of irritable bowel syndrome has been reported in many pelvic pathologies,5 6 and even on strict adherence to Manning and Rome criteria I and II for case definition of irritable bowel syndrome the percentage of concordance is low 7. The diagnosis of irritable bowel syndrome is a diagnosis of exclusion, especially when red flag signs are present.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies routinely used the Manning, Rome I, or Rome II criteria to diagnosis the tested subjects, of which the Rome II criteria have been mainly used in more recent epidemiological studies. The earlier Manning criteria are more general and less restrictive than the more recent Rome I and Rome II criteria, and several studies have revealed that the prevalence rates of IBS evaluated by the Manning criteria are relatively higher than those evaluated by the Rome criteria [5,25,26]. Data from recent epidemiological studies evaluated by the Rome II criteria are summarized in Table 1 [25,[27][28][29][30][31][32][33][34][35][36][37].…”
Section: Prevalence Of Ibsmentioning
confidence: 99%